Preschool Experience as Predictor of Language Learning Outcomes among a Sample of Grades 1, 2, and 3 Students in Bahrain - Arora, Bani; Mukalid, Samar Habib; Fateel, Moosa Jaafar (Journal of Education and e-Learning Research, 2022)
The aim of the present study was to examine the effects of preschool experience on academic achievement, with specific reference to English language learning outcomes of Grades 1, 2 and 3 students in the Kingdom of Bahrain. Data from a representative sample of 402 students covering all three grades, from Bahrain public elementary schools were statistically analyzed using mean scores, t-test and one-way ANOVA test. The findings of the study revealed consistently higher mean scores in all the three grades for students who attended preschool compared with those who did not attend preschool. There was no significant difference found in ANOVA scores within the grades. The authors of this study recommend extensive research and the integration of pre schools with elementary schools as part of compulsory education; a national level quality measurement system is also recommended for a better future of the nation.